Tropical Foliage Plant Development: Origin of New Cultivars - Richard J. Henny; Jianjun Chen (EDIS, 2008)
ENH-1092, a 5-page illustrated fact sheet by R.J. Henny and J. Chen, describes three avenues for new tropical foliage plants to enter the commercial trade — plant acquisition and collection from the wild, selection of natural or induced mutations, and hybridization — and how new introductions are evaluated. Includes references. Published by the UF Department of Environmental Horticulture, January 2008.